A rare subepithelial lesion in the stomach: Gastric adenomyoma. Issue 2 (25th March 2021) - Abbasov, Aykhan; Aslan, Ekrem; Ekici, Asiye Isin Dogan; Dolay, Kemal
Abstract: Gastric adenomyomas are rare benign tumours and most often localized in the gastric antrum. The tumour generally consists of glandular cells and smooth muscle bundles. The size of a gastric adenomyoma (GA) can be up to 4.5 cm and can affect patients any age of their life. In cases with GA most of the patients are asymptomatic. However, non‐specific gastrointestinal symptoms such as epigastric pain, vomiting and nausea can be seen. Differential diagnosis of GA difficult due to non‐specific radiological and endoscopic findings. Imaging techniques and endoscopic examinations can not distinguish GAs from other intramuscular lesions of the stomach. Surgical excision is used in both diagnosis and treatment. In this article, we present a 46‐year‐old male patient with long‐term dyspeptic complaints admitted to our department and diagnosed as gastric adenomyoma by performing subtotal gastrectomy.